Injuries in men's international ice hockey: a 7-year study of the International Ice Hockey Federation Adult World Championship Tournaments and Olympic Winter Games. Issue 1 (7th October 2014) - Tuominen, Markku; Stuart, Michael J; Aubry, Mark; Kannus, Pekka; Parkkari, Jari
Abstract : Background: Information on ice hockey injuries at the international level is very limited. The aim of the study was to analyse the incidence, type, mechanism and severity of ice hockey injuries in men's international ice hockey tournaments. Methods: All the injuries in men's International Ice Hockey Federation World Championship tournaments over a 7-year period were analysed using a strict definition of injury, standardised reporting strategies and an injury diagnosis made by a team physician. Results: 528 injuries were recorded in games resulting in an injury rate of 14.2 per 1000 player-games (52.1/1000 player-game hours). Additionally, 27 injuries occurred during practice. For WC A-pool Tournaments and Olympic Winter Games (OWG) the injury rate was 16.3/1000 player-games (59.6/1000 player-game hours). Body checking, and stick and puck contact caused 60.7% of the injuries. The most common types of injuries were lacerations, sprains, contusions and fractures. A laceration was the most common facial injury and was typically caused by a stick. The knee was the most frequently injured part of the lower body and the shoulder was the most common site of an upper body injury. Arenas with flexible boards and glass reduced the risk of injury by 29% (IRR 0.71, (95% CI 0.56 to 0.91)). Conclusions: The incidence of injury during international ice hockey competition is relatively high. Arena characteristics, such as flexible boards and glass, appeared to reduce the risk of injury.